2003
DOI: 10.17221/4085-pse
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genetic variability in bamboo using RAPD markers

Abstract: Classical taxonomic studies of the bamboos are based on floral morphology and growth habit, which can cause problems in identification due to erratic flowering. Identification and genetic relationships in 12 species of bamboo were investigated using random amplified polymorphic DNAs (RAPD) technique. Analysis started by using thirty 10-mer primers that allowed us to distinguish 12 species and to select a reduced set of primers. The selected primers were used for identification and for establishing a profiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 14 publications
(9 reference statements)
3
35
0
1
Order By: Relevance
“…One inherent difference of the screening of RAPD and RAPD-RFLP markers, however, was that the RAPD-RFLP markers were run on an acrylamide gel, which enables the detection of higher number of loci, usually with potential of detecting bands with even less than 100 bp with sufficient resolution for distinction. RAPD markers have been used in studies aimed at the analysis of genetic diversity and divergence among bamboos (Nayak et al 2003;Lalhruaitluanga and Prasad 2009;Shalini et al 2013). Despite these markers have been argued about their limitations, such as their dominance, uncertain locus homology and sensitivity to the conditions of the PCR reactions (Yeasmin et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One inherent difference of the screening of RAPD and RAPD-RFLP markers, however, was that the RAPD-RFLP markers were run on an acrylamide gel, which enables the detection of higher number of loci, usually with potential of detecting bands with even less than 100 bp with sufficient resolution for distinction. RAPD markers have been used in studies aimed at the analysis of genetic diversity and divergence among bamboos (Nayak et al 2003;Lalhruaitluanga and Prasad 2009;Shalini et al 2013). Despite these markers have been argued about their limitations, such as their dominance, uncertain locus homology and sensitivity to the conditions of the PCR reactions (Yeasmin et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…First, for molecular identification and phylogenetic relationships, RAPD markers were used for distinguishing species of the genera Bambusa, Dendrocalamus, Dinocloa and Cephalostachyum (Nayak et al 2003). Two specific RAPD markers from Bambusa balcooa Roxb.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrograms were constructed using the UPGMA algorithms in the MEGA 4.0 software (Tamura et al, 2007) and showed that the phylogenetic tree was divided into two major clusters. Nayak et al(2003) and this easy reproducibility of results obtained from intersimple sequence repeat makes it most reliable molecular markers based method as it permits detection of polymorphisms in inter-microsatellite loci, using a primer designed from dinucleotide or trinucleotide simple sequence repeats. ISSR markers have been extensively used for DNA finger-printing (Moreno et al, 1998), population genetics studies (Nebauer et al, 1999) and phylogenetic studies (Hess et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional method of identifying species by morphological characters linked with DNA profiling can be useful for the clarification of taxonomic position. DNA profiling through RAPD markers has been used for the diversity analysis and duplicates identification within the large germplasm population (Nayak et al 2003) identification of varieties/species (Prince et al 1995), phylogenetic relationship (Nair et al 1999) and conservation and management of genetic resources (Bretting & Widrelechner 1995). Evidently, RAPD technology is a rapid and sensitive technique, which can be used to estimate relationships between closely and more distantly related species of Chlorophytum.…”
Section: Discussionmentioning
confidence: 99%